A Novel Multiplayer Screen-Based Simulation Experience for African Learners Improved Confidence in Management of Postpartum Hemorrhage - Taekman, Jeffrey M.; Foureman, Megan F.; Bulamba, Fred; Steele, Michael; Comstock, Emily; Kintu, Andrew; Mauritz, Amy; Olufolabi, Adeyemi (Frontiers in Public Health, 2017)
Introduction Postpartum hemorrhage (PPH) remains a global challenge, affecting thirteen million women each year. In addition, PPH is a leading cause of maternal mortality in Asia and Africa. In the U.S.A., care of critically ill patients is often practiced using mannequin-based simulation. Mannequin-based simulation presents challenges in global health, particularly in low- or middle-income countries. We developed a novel multiplayer screen-based simulation in a virtual world enabling the practice of team coordination with PPH. We used this simulation with learners in Mulago, Uganda. We hypothesized that a multiplayer screen-based simulation experience would increase learner confidence in their ability to manage PPH. Methods The study design was a simple pre- and a post-intervention survey. Forty-eight interprofessional subjects participated in one of nine 1-h simulation sessions using the PPH software. A fifteen-question self-assessment administered before and after the intervention was designed to probe the areas of learning as defined by Bloom and Krathwohl: affective, cognitive, and psychomotor. Results Combined confidence scores increased significantly overall following the simulation experience and individually in each of the three categories of Bloom’s Taxonomy: affective, cognitive, and psychomotor. Conclusion We provide preliminary evidence that multiplayer screen-based simulation represents a scalable, distributable form of learning that may be used effectively in global health education and training. Interestingly, despite our intervention being screen-based, our subjects showed improved confidence in their ability to perform psychomotor tasks. Although there is precedent for mental rehearsal improving performance, further research is needed to understand this finding.